GSIM Measurement of the Costs of Protection in Southeast Europe - Mario Holzner (The Vienna Institute for International Economic Studies (wiiw), 2004)
In this paper, the global simulation model (GSIM) by Francois and Hall (2003) for the analysis of global, regional and unilateral trade policy changes was applied to the countries of Southeast Europe in order to measure the costs of protection in the region. The model is a multiregion, imperfect substitutes model of world trade employing a partial equilibrium approach. After using regional data on trade and initial and final tariffs (a `2020 SEE-EUaccession and world-wide-tariff-reduction' scenario was assumed) and elasticities, the following output is being estimated trade effects, welfare effects (producer surplus, consumer surplus and change in tariff revenue) and price and output changes. As expect ed, most of the changes in net welfare after a full liberalization of trade in the Balkans and between Southeast Europe and the EU are likely to emerge in those sectors where the SEE countries have specialized and protection is strong agriculture, food processing and the textiles industry. For many of the SEE countries, trade liberalization will lead to a substantial loss of tariff revenues. However, this should be outweighed by an even stronger increase of consumer surplus due to substantially reduced consumer prices. The overall consumer surplus for the Balkans is estimated at more than USD 5 billion or 4% of 2002 GDP as against an overall SEE loss of tariff revenues of approximately USD 2 billion or about 1.6% of 2002 GDP.
Keywords: F13; F15; F17; 330; Costs of Protection; Partial Equilibrium Model; Trade Policy Modelling; Simulation Model; International Trade; Southeastern Europe